2017
DOI: 10.1183/13993003.00354-2017
|View full text |Cite
|
Sign up to set email alerts
|

More on idiopathic pulmonary arterial hypertension with a low diffusing capacity

Abstract: Pulmonary arterial hypertension (PAH) is defined by the presence of pre-capillary pulmonary hypertension (PH) in the absence of underlying causes such as lung diseases, chronic thromboembolic pulmonary hypertension (CTEPH) or other rare conditions [1,2]. While the idiopathic form of PAH (IPAH) was originally described as a disease affecting primarily younger women [3,4], it is now increasingly being diagnosed in elderly patients, many of whom present with cardiopulmonary comorbidities, which can make the exact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 14 publications
(15 reference statements)
3
24
0
6
Order By: Relevance
“…16, 29 −31 Apparently, this pulmonary vasculopathy can develop in patients with or without clinical and radiological signs of parenchymal lung disease. 29 Patients in Cluster 3 had a particularly poor survival, which is consistent with previous reports on patients with IPAH and low DLCO. 16,29,31 Further studies are needed to delineate the mechanisms underlying the survival differences between the clusters.…”
Section: Discussionsupporting
confidence: 91%
“…16, 29 −31 Apparently, this pulmonary vasculopathy can develop in patients with or without clinical and radiological signs of parenchymal lung disease. 29 Patients in Cluster 3 had a particularly poor survival, which is consistent with previous reports on patients with IPAH and low DLCO. 16,29,31 Further studies are needed to delineate the mechanisms underlying the survival differences between the clusters.…”
Section: Discussionsupporting
confidence: 91%
“…Whilst they included patients who had mild or moderate lung disease, we observed a similar distribution of DLCO %predicted in patients without any lung disease (IPAH no-LD , online supplement figure 2). Olsson et al subsequently described a subgroup of patients with IPAH with no parenchymal lung disease but severely reduced gas transfer (23). In keeping with these two studies, our cohort of IPAH no-LD patients with DLCO <45%predicted (IPAH DLCO<45 ) was older, more likely to have a smoking history and had a lower exercise capacity.…”
Section: Ipah With Dlco <45%supporting
confidence: 74%
“…Similarly, Olsson's study suggested that elderly I/H-PAH patients, who had a greater smoking history and more parenchymal lung disease, had a lower %DLco and more hypoxemia. They suggested that smoking damaged the capillaries of the lung, causing lower %DLco and poor oxygenation 3 .…”
Section: Discussionmentioning
confidence: 99%